Sudden Stops and IMF-Supported Programs - Eichengreen, Barry (IMF Working Papers; Working Paper, 2006)
Could a high-access, quick-disbursing "insurance facility" in the IMF help to reduce the incidence of sharp interruptions in capital flows ("sudden stops")? We contribute to the debate around this question by analyzing the impact of conventional IMF-supported programs on the incidence of sudden stops. Correcting for the non-random assignment of programs, we find that sudden stops are fewer and generally less severe when an IMF arrangement exists and that this form of "insurance" works best for countries with strong fundamentals. In contrast there is no evidence that a Fund-supported program attenuates the output effects of capital account reversals if these nonetheless occur.